An automated imaging system for radiation biodosimetry. Issue 7 (4th May 2015) - Garty, Guy; Bigelow, Alan W.; Repin, Mikhail; Turner, Helen C.; Bian, Dakai; Balajee, Adayabalam S.; Lyulko, Oleksandra V.; Taveras, Maria; Yao, Y. Lawrence; Brenner, David J.
ABSTRACT We describe here an automated imaging system developed at the Center for High Throughput Minimally Invasive Radiation Biodosimetry. The imaging system is built around a fast, sensitive sCMOS camera and rapid switchable LED light source. It features complete automation of all the steps of the imaging process and contains built‐in feedback loops to ensure proper operation. The imaging system is intended as a back end to the RABiT—a robotic platform for radiation biodosimetry. It is intended to automate image acquisition and analysis for four biodosimetry assays for which we have developed automated protocols: The Cytokinesis Blocked Micronucleus assay, the γ‐H2AX assay, the Dicentric assay (using PNA or FISH probes) and the RABiT‐BAND assay. Microsc. Res. Tech. 78:587–598, 2015. © 2015 Wiley Periodicals, Inc.